2008
DOI: 10.1029/2007gl032722
|View full text |Cite
|
Sign up to set email alerts
|

Observation of isolated high‐speed auroral streamers and their interpretation as optical signatures of Alfvén waves generated by bursty bulk flows

Abstract: The THEMIS All‐Sky Imager at Fort Smith, Canada observed a sudden appearance and subsequent evolution of auroral streamers on April 15, 2006. The event took place in an oval that was optically dark, and evolved into a 20‐minute period of intense equatorward streaming of red aurora. We characterize the incipient event as isolated streamers, a phenomenon previously linked with bursty bulk flows in the plasma sheet. Thanks to the high time and spatial resolution of THEMIS ASI, the observed streamer reveals some d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
(18 reference statements)
1
17
0
Order By: Relevance
“…The auroral feature reported here moved westward and poleward first to be followed by an equatorward‐dawnward retreat. Just like the phenomenon by Liu et al [2008], this observation was revealed by the highly sensitive NORSTAR (NORthern Solar Terrestrial ARray) All‐Sky Imager at Rankin Inlet (72.41/335.74 geomag. lat./long.)…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…The auroral feature reported here moved westward and poleward first to be followed by an equatorward‐dawnward retreat. Just like the phenomenon by Liu et al [2008], this observation was revealed by the highly sensitive NORSTAR (NORthern Solar Terrestrial ARray) All‐Sky Imager at Rankin Inlet (72.41/335.74 geomag. lat./long.)…”
Section: Introductionmentioning
confidence: 57%
“…As discussed in the Introduction section, almost all previous reports of auroral streamers showed equatorward motion only [e.g., Rostoker et al , 1987; Henderson et al , 1998]. The only exception is the report by Liu et al [2008] who showed a low‐latitude poleward streamer moving poleward to meet a high‐latitude streamer moving equatorward. They associated both streamers with earthward flows in the magnetotail and attributed the poleward motion of the streamer to the propagation time delay of Alfvén waves from the source region to the ionosphere.…”
Section: Summary and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although not reviewed here, because they lack observational confirmation, it is worth noting that other auroral features have been proposed to be caused by Alfvén waves. For example, Liu et al (2008) proposed that Alfvén waves generated by BBFs are the cause of auroral streamers.…”
Section: Location Of Alfvénic Auroramentioning
confidence: 99%
“…Lyons et al (1999) claimed that PBIs are the result of the mapping to the ionosphere of the localized enhanced dawn-to-dusk electric fields that give rise to BBFs within the plasma sheet, as suggested by Henderson et al (1998). An observation of auroral streamers moving poleward at the same time that other auroral streamers moved equatorward from a PBI led Liu et al (2008) to propose a revised explanation. Alfvén waves generated by the BBFs were suggested to cause the auroral streamers.…”
Section: T Johansson Et Al: Electric Field Associated With a Bbf-limentioning
confidence: 99%